2007
DOI: 10.1371/journal.pone.0001312
|View full text |Cite
|
Sign up to set email alerts
|

SAVVY® (C31G) Gel for Prevention of HIV infection in Women: A Phase 3, Double-Blind, Randomized, Placebo-Controlled Trial in Ghana

Abstract: ObjectiveThe objective of this trial was to determine the effectiveness of 1.0% C31G (SAVVY) in preventing male-to-female vaginal transmission of HIV infection among women at high risk.Methodology/Principal FindingsThis was a Phase 3, double-blind, randomized, placebo-controlled trial. Participants made up to 12 monthly visits for HIV testing, adverse event reporting, and study product supply. The study was conducted between March 2004 and February 2006 in Accra and Kumasi, Ghana. We enrolled 2142 HIV-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
122
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(127 citation statements)
references
References 11 publications
3
122
1
1
Order By: Relevance
“…The premature closure of several narrow-spectrum-microbicide human clinical trials underscores the challenges in microbicide development. The increase in HIV infection among women using nonoxynol-9 (N-9), Savvy (33), or cellulose sulfate highlights the need for improved preclinical evaluation of both the safety and the efficacy of candidate microbicides (15,41). Specifically, efficacy studies must include a more extensive evaluation of the activities of candidate drugs against HIV isolates representing multiple clades in cell and explant culture systems reflective of the genital tract.…”
mentioning
confidence: 99%
“…The premature closure of several narrow-spectrum-microbicide human clinical trials underscores the challenges in microbicide development. The increase in HIV infection among women using nonoxynol-9 (N-9), Savvy (33), or cellulose sulfate highlights the need for improved preclinical evaluation of both the safety and the efficacy of candidate microbicides (15,41). Specifically, efficacy studies must include a more extensive evaluation of the activities of candidate drugs against HIV isolates representing multiple clades in cell and explant culture systems reflective of the genital tract.…”
mentioning
confidence: 99%
“…This poorly understood process cannot be properly evaluated in vitro. The recent failure and enhanced transmission observed in the first microbicide efficacy trials with nonoxynol-9 and Savvy [193,194] warrant the need for controlled and careful investigation of topical products in animal models. A phase II/III trial with nonoxynol-9, an over the counter spermicide, in a vaginal gel formulation increased the risk of acquisition of HIV among users of the gel [195].…”
Section: The Role Of the Nhp Model For Pre-exposure Prophylaxismentioning
confidence: 99%
“…Such populations, however, can be challenging to identify and recruit into clinical trials. Recruitment approaches reported most often in pre-exposure prophylaxis (PrEP), vaginal microbicide, and HIV vaccine clinical trials include recruiting from community venues such as markets, education institutions, bars, and hotels/hostels; [1][2][3][4][5][6][7] from health facilities such as family planning, sexually transmitted infection (STI), and primary care clinics; [4][5][6][7][8][9][10][11] through peer recruiters; 6,9,11 and through strategies combining geography and sexual network characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…We began planning for FEM-PrEP soon after the completion of the SAVVY trials in West Africa, also sponsored by FHI 360. 1,2 Investigators from these trials reported that they were unable to determine the effectiveness of the study product because of lower than expected HIV incidence within the study population. With this in mind, and building upon FHI 360's previous PrEP clinical trial formative research, we conducted formative research in three of the four FEM-PrEP sites (Bondo, Pretoria, and Arusha) to inform the FEM-PrEP recruitment strategy by identifying places where HIV incidence might be high.…”
mentioning
confidence: 99%